Highly porous, soft, and flexible vapor-phase polymerized polypyrrole–styrene–ethylene–butylene–styrene hybrid scaffold as ammonia and strain sensor. Issue 38 (12th June 2020) - Fernandez, Frances Danielle M.; Khadka, Roshan; Yim, Jin-Heong
Abstract : Fabrication of a hybrid scaffold from an oxidant-impregnated styrene–ethylene–butylene–styrene (SEBS) matrix comprising a three-dimensional sugar particle assembly by vapor phase polymerization (VPP). Abstract : Herein, in situ vapor-phase polymerization (VPP) of pyrrole on an oxidant-impregnated styrene–ethylene–butylene–styrene (SEBS) matrix comprising a three-dimensional sugar particle assembly was used to produce a soft and porous polypyrrole (PPy)–SEBS hybrid scaffold. Characterization of the PPy–SEBS hybrid scaffold using field-effect scanning electron microscopy, Fourier-transform infrared spectroscopy, energy-dispersive X-ray spectroscopy, and micro-computerized tomography confirmed the successful uniform and homogenous polymerization of PPy onto the SEBS matrix with a porous morphology. The performance of the hybrid scaffold of different pore sizes as an ammonia sensor under different temperature conditions was evaluated in terms of resistance change. The results showed that the PPy–SEBS scaffolds of larger pore size had higher resistance changes under lower temperature conditions when ammonia (NH3 ) gas was introduced compared to those observed for smaller pore sizes under higher temperature conditions. These scaffolds showed excellent repeatability and reversibility in detecting NH3 gas with fast response and recovery times of 30 s and 10–15 min, respectively. Moreover, the larger pore size scaffolds polymerized for a longer time possessed a remarkable ability to be applied as strain sensors. These kinds of novel, soft, and porous conductive polymer composite materials produced by VPP will have huge practical applications in monitoring other toxic and non-toxic gases.